Immigrants' Rights in the Courts and Congress: Constitutional Protections and the Rule of Law After 9/11 - Lucas Guttentag (Washington University Journal of Law & Policy, 2007)
We all witnessed the astonishing demonstrations across the country in the spring of 2006. We watched with surprise as legislation recently was passed by the U.S. Senate to address a dysfunctional immigration system. The so-called comprehensive immigration reform bill held out the promise of legal status to millions of undocumented immigrants and suggested it would do something for the additional millions who are stuck in an immigration backlog despite being eligible for legal status. That was the hope, but it also camouflaged grave deficiencies. My goal is to draw attention to some of those shortcomings, to put them into the context of 9/11 and recent legislation as well as our historic attitudes, and to focus on the essential need to preserve and restore effective judicial review as a cornerstone of immigrants’ rights.
Keywords: Civil rights; Aliens (Persons); Immigration reform; Social justice; Rule of law; Deportation; Illegal immigrants; Race discrimination; Illegal Immigration Reform and Immigrant Responsibility Act of 1996; United States